2013
DOI: 10.5334/jpl.81
|View full text |Cite
|
Sign up to set email alerts
|

L2 acquisition of English present perfect interpretations

Abstract: The present study investigates the role of first language (L1), in our case Cypriot Greek (CG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Admittedly, tense plays the most crucial part of the grammar of a language. It is, undeniably, challenging for nonnative learners who spend a long time before they can use tenses correctly (Croft, 2012;Frederickson, 1997;Halliday, 2002;Karpava & Agouraki, 2013;Lado, 1975;Noochoochai, 1978;Ockenden, 1967;Sholeha, Ardian, & Amri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Admittedly, tense plays the most crucial part of the grammar of a language. It is, undeniably, challenging for nonnative learners who spend a long time before they can use tenses correctly (Croft, 2012;Frederickson, 1997;Halliday, 2002;Karpava & Agouraki, 2013;Lado, 1975;Noochoochai, 1978;Ockenden, 1967;Sholeha, Ardian, & Amri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In English, the PPT covers actions that happened in the past that have resulted in the present speaking about such actions. Establishing this connection between the past and present is, arguably, a good strategy to absorb in them the notion of the PPT and thus avoid mistakes and confusion in using such a tense (Karpava & Agouraki, 2013).…”
Section: Teaching Tenses To L2 Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…The present perfect is considered "one of the most semantically complex verb forms" (Kearns, 2011, p. 182) since it can be used to convey several meanings (Comrie, 1975;Eastwood, 1995;Greenbaum & Nelson, 2002;Kearns, 2011;Quirk, Greenbaum, Leech, & Svartvik, 1985). This complex nature of the present perfect may be the reason why the present perfect is likely to cause difficulties for second language learners (Han & Hong, 2015;Karpava & Agouraki, 2013;Thumvichit, 2016). As an example, it has been found that second language learners tend to convey the present perfect meanings in other tenses in English, e.g.…”
mentioning
confidence: 99%
“…That is, they focus on how learners use the present perfect (see e.g. Arakkitsakul, 2008;Han & Hong, 2015;Karpava & Agouraki, 2013;Patanasorn, 2013;Payre-Ficout, Brissaud, & Chevrot, 2009;Petchtae, 2011;Thumvichit, 2016;Yoshimura et al, 2014). Few studies have concentrated on such input for learners as textbooks, which are considered as a key component in language learning and teaching (Richards, 2001).…”
mentioning
confidence: 99%